A Simulation-Based Approach for the Automated Design of Fatigue Resistant Continuous Fibre-Reinforced Components - Gadinger, Marc; Bode, Christoph; Deutschmann, Torben; Krause, Dieter; Wartzack, Sandro (Proceedings of the 35th Symposium Design for X (DFX2024), 2024)
Fibre-reinforced plastics are increasingly being used in important structural components. Here they are often subjected to cyclic loading, which leads to a deterioration in material properties. However current design methods hardly take this fatigue behavior into account. Instead, they rely on conservative safety factors, resulting in over-dimensioned components. In order to realise the full lightweight potential, we propose an innovative method that enables a targeted design for a defined service life. It integrates knowledge from experimental fatigue testing and uses modified mathematical failure criteria to predict the degree of fatigue throughout the part. This allows us to adaptively reinforce fatigue critical areas, resulting in lightweight and fatigue resistant structure
Keywords: fatigue behavior; fibre-reinforced plastics; lightweight design; optimization